2019
DOI: 10.3389/fnagi.2018.00438
|View full text |Cite
|
Sign up to set email alerts
|

Increased DJ-1 and α-Synuclein in Plasma Neural-Derived Exosomes as Potential Markers for Parkinson’s Disease

Abstract: The diagnosis of PD might be in difficulty, especially in the early stages. Therefore, the identification of novel biomarkers is imperative for the diagnosis and monitoring disease progression in PD. DJ-1 and α-synuclein, are two proteins that are critically involved in the pathogenesis of PD, and they have been examined as disease biomarkers in studies. However, no study exists regarding DJ-1 in plasma neural-derived exosomes. In the present study, the levels of DJ-1 and α-synuclein in plasma neural-derived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 44 publications
6
129
2
Order By: Relevance
“…Both, DJ-1 and α-synuclein were significantly higher in neuronal exosomes from patients with PD than in those from healthy controls whereas no significant differences were observed in total plasma, in agreement with the previous study by Shi et al (2014). As in the previous study, ROC analysis yielded only a moderate discrimination between patients with PD and healthy controls even when both biomarkers were combined (Zhao et al, 2019).…”
Section: Cns-derived Exosomes As a Source Of Biomarkers For Neurodegesupporting
confidence: 91%
See 2 more Smart Citations
“…Both, DJ-1 and α-synuclein were significantly higher in neuronal exosomes from patients with PD than in those from healthy controls whereas no significant differences were observed in total plasma, in agreement with the previous study by Shi et al (2014). As in the previous study, ROC analysis yielded only a moderate discrimination between patients with PD and healthy controls even when both biomarkers were combined (Zhao et al, 2019).…”
Section: Cns-derived Exosomes As a Source Of Biomarkers For Neurodegesupporting
confidence: 91%
“…Recently, the protocol developed by Goetzl et al was used by another group to determine the levels of DJ-1 and α-synuclein in neuronal exosomes from 39 patients with PD and 40 healthy controls (Zhao et al, 2019). Both, DJ-1 and α-synuclein were significantly higher in neuronal exosomes from patients with PD than in those from healthy controls whereas no significant differences were observed in total plasma, in agreement with the previous study by Shi et al (2014).…”
Section: Cns-derived Exosomes As a Source Of Biomarkers For Neurodegesupporting
confidence: 77%
See 1 more Smart Citation
“…Comparisons of receiver operating characteristic results showed that neuronal exosomal α‐syn in our study had a greater power for diagnosing early‐stage PD. Other groups have reported mean values of 7.75 pg/mL by enzyme‐linked immunosorbent assay [12] or 25 pg/mL by Luminex [6] of α‐syn in plasma neuronal exosomes from patients with PD. We found a mean level of 2066 pg/mL of α‐syn using electrochemiluminescence immunoassay, which was reported to have a higher sensitivity and a larger dynamic range than traditional enzyme‐linked immunosorbent assay or Luminex [13].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, erythrocytes can provide complementary information to plasma/serum biomarkers [25]. The implementation of blood-based biomarker panels with plasma neurally-derived exosomes and miRNA, besides the already established candidate molecules, may constitute the basis of a blood-based 'liquid biopsy' [26,27], following the encouraging developments of liquid biopsies in oncology.…”
Section: Peripheral Exosomes and Micrornas As Novel Research Field Inmentioning
confidence: 99%